Incidentally exploring natural course of a rare entity: representative case for rosette-forming glioneuronal tumors - Altunbüker, Hira; Hinz, Felix; Sahm, Felix; Brehmer, Stefanie; Wenz, Holger (Neurological sciences, 2023)
Rosette-forming glioneuronal tumors (RGNT) are extremely rare mostly benign tumors of the central nervous system, which are often studied for its histological aspects despite relatively small numbers of clinical especially radiological knowledge.